2018
DOI: 10.1111/cdoe.12415
|View full text |Cite
|
Sign up to set email alerts
|

Impact of oral health literacy on self‐reported missing data in epidemiological research

Abstract: Participants with lower OHL were significantly more likely to fail to complete research questionnaires. The impact of OHL on missing data was greater with more complex types of items.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
6
8
0
Order By: Relevance
“…In turn, better performance from the educational intervention of parents with adequate OHL compared to parents with inadequate/marginal OHL is consistent with the results of other studies [16,17,[36][37][38][39][40][41][42], which found an association of lower OHL levels with the highest rates of missing dental appointments, worse oral health conditions in adults, worse perceived oral health of their children, poor oral health outcomes in their children, negative health attitudes, less adherence to recommendations for healthy habits, greater difficulty filling out questionnaires.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In turn, better performance from the educational intervention of parents with adequate OHL compared to parents with inadequate/marginal OHL is consistent with the results of other studies [16,17,[36][37][38][39][40][41][42], which found an association of lower OHL levels with the highest rates of missing dental appointments, worse oral health conditions in adults, worse perceived oral health of their children, poor oral health outcomes in their children, negative health attitudes, less adherence to recommendations for healthy habits, greater difficulty filling out questionnaires.…”
Section: Discussionsupporting
confidence: 90%
“…The average BREALD-30 score in this study was 21.6, similar to that found in other studies developed in the state of Paraná, of 21.9 [36] and 22.3 [17]. The first of these was also involving parents/caregivers of children, in this case, aged 4-5 years and enrolled in public schools in the city of Curitiba [36]. The second study examined a sample of 175 pregnant women and evaluated their acquisition and retention of information about nutrition and oral hygiene of children under 2 years old, with a follow-up of up to 4 weeks.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Increasing evidence has indicated the OHL is associated with socioeconomic characteristics while our findings also revealed that individuals with older age, lower educational level, and lower monthly income performed inadequate OHL. These results were consistent with previous studies (Batista, Lawrence, & Sousa, 2017;Firmino et al, 2018;Vyas et al, 2016).…”
Section: Discussionsupporting
confidence: 94%